The world Polleniidae (Diptera, Oestroidea): key to genera and checklist of species - Silvia Gisondi; Knut Rognes; Davide Badano; Thomas Pape; Pierfilippo Cerretti (ZooKeys, 2020)
A key to the world genera and a checklist of the world species for the family Polleniidae, including distributions, are provided. The following taxonomic and nomenclatural changes are proposed: Nitellia hermoniella Lehrer, 2007 = Pollenia mediterranea Grunin, 1966, syn. nov., Pollenia bentalia Lehrer, 2007 = Pollenia semicinerea Villeneuve, 1911, syn. nov., Dasypoda angustifrons Jacentkovský, 1941 = Pollenia tenuiforceps Séguy, 1928, syn. nov.; Anthracomyza Malloch, 1928, resurrected name (monotypic; type species Anthracomyia atratula Malloch) is considered a valid name and tentatively assigned to Polleniidae, giving Anthracomyza atratula (Malloch, 1927) as a resurrected combination; Morinia crassitarsis (Villeneuve, 1936), stat. rev. is considered a valid species, and Micronitellia Enderlein, 1936, stat. nov. is considered an available name.